Why public health framing matters: An experimental study of the effects of COVID-19 framing on prejudice and xenophobia in the United States - Dhanani, Lindsay Y.; Franz, Berkeley (Social science & medicine (1982), 2021)
The COVID-19 pandemic has triggered a notable increase in the expression of prejudicial and xenophobic attitudes that threaten the wellbeing of minority groups and contribute to the overall public health toll of the virus. However, while there is evidence documenting the growth in discrimination and xenophobia, little is known about how the COVID-19 outbreak is activating the expression of such negative attitudes. The goal of the current paper therefore was to investigate what aspects of the COVID-19 pandemic may be contributing to this rise in expressions of prejudice and xenophobia. More specifically, this study used an experimental design to assess the effects of using stigmatized language to describe the virus as well as the threat to physical health and economic wellbeing posed by the virus on COVID-19 prejudice. Data were collected from a national sample of 1451 adults residing within the United States. Results from 2 × 2 x 2 between-subjects analyses of covariance demonstrated that emphasizing the connection between China and COVID-19, rather than framing the virus neutrally, increased negative attitudes toward Asian Americans, beliefs that resources should be prioritized for Americans rather than immigrants, and general xenophobia. Emphasizing the severity of the economic impact of the virus also increased beliefs that Asian Americans are a threat to resources and general xenophobia. In contrast, messages which emphasized the serious health risks of COVID-19 did not increase bias toward Asian Americans or xenophobia. Our findings suggest that specific types of public health messaging related to infectious diseases, especially framing the virus in terms of its country of origin or its likely economic impact, may elicit prejudice and xenophobia. Public health campaigns that emphasize the severity of the virus, however, are not likely to trigger the same negative attitudes. Implications for public health responses to health crises are discussed. •The framing of COVID-19 information shapes prejudice and xenophobia.•Emphasizing COVID-19's origin in China increases anti-Asian and xenophobic attitudes.•Emphasizing severe economic harm also increases negative outgroup attitudes.•Messaging about the health threat of the virus is unrelated to outgroup bias.